Direito Penal Tributário: da norma jurídica prevista no artigo 1º da Lei nº 8.137/90 e a extinção da punibilidade pelo pagamento - Ferreira, Ana Lya Ferraz da Gama (2016)
This thesis has as its primary purpose the study about tax criminal legal norm, its incidence, structure and appliance. It is seeking an interdisciplinary study about the theme through the evaluation of the Criminal Law standards and Tributary Law, taking off the structure of applicable matrix rules in each one of those branches to, posteriorly, apply it in the study of tax criminal standard predicted in article 1st of Law #8.137/90, that dispose about the tributary crimes. The criminology presents studies about the theme that justify the reason for what criminality related to the white collar crimes is not widespread neither stigmatized in the society. Even before the relevancy of the legal interests protected by the Criminal Law in tributary crimes, there is in the planning an extinctive cause of criminality applied when the defendant discharge from objects of withholding. In those cases, it privileges the collecting interests over the protected legal benefit. Moreover, the appliance of this extinctive cause breaches evidently the principle of equality, because it only benefits the ones with sufficient economic capacity to pay for the extinction of your criminal liability